COMPARISON OF TWO JACUZZIS AND SWIMMING MILD RECOVERIES ON HEART BEAT RATE AND MYOCARDIAL OXYGEN CONSUMPTION OF SWIMMING - Aminian, Ensiyeh (2015)
http://dx.doi.org/10.5902/2179460X19445Main aim of this research was comparing effect of two Jacuzzis, swimming mild recoveries on heart beat rate, and myocardial oxygen cost of swimming. Initially normal data distribution Kolmogorov Smirnov test was used in order to reflect the normal distribution of data. For data analysis descriptive statistics were used (placebo, median, mean, variance, and standard deviation) in order to compare changes of Lactic acid of heart rate beat and consumption oxygen of myocardial. Therefore, we used t student, alpha error is 0.05, and Excel 2007 and SPSS 18 did analysis. Result of research indicated that inactive recovery was effective on faster excreted lactic acid. Moreover, results of research indicated that recovery on mild swim Jacuzzi was effective on heart rate, myocardial consumption of oxygen. In addition, results of research indicated that heart rate and myocardial consumption of oxygen reduce in Jacuzzi recovery.